OsDWARF10, transcriptionally repressed by OsSPL3, regulates the nutritional metabolism of polished rice - Li, Kang; Cheng, Yan; Fang, Chuanying (Frontiers in Plant Science, 2023)
Strigolactones (SL) play essential roles in plant development and the metabolism of rice leaves. However, the impact of SL on the accumulation of nutritional metabolites in polished rice, as well as the transcription factors directly involved in SL synthesis, remains elusive. In this study, we performed a metabolome analysis on polished rice samples from mutants of an SL biosynthetic gene, OsDWARF10 (OsD10). Compared with those in the wild type plants, primary and secondary metabolites exhibited a series of alterations in the d10 mutants. Notably, the d10 mutants showed a substantial increase in the amino acids and vitamins content. Through a yeast one-hybridization screening assay, we identified OsSPL3 as a transcription factor that binds to the OsD10 promoter, thereby inhibiting OsD10 transcription in vivo and in vitro. Furthermore, we conducted a metabolic profiling analysis in polished rice from plants that overexpressed OsSPL3 and observed enhanced levels of amino acids and vitamins. This study identified a novel transcriptional repressor of the SL biosynthetic gene and elucidated the regulatory roles of OsSPL3 and OsD10 on the accumulation of nutritional metabolites in polished rice.